Method for preparing niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate by electrochemical deposition method and application of niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate
The preparation of niobium doped amorphous carbon composite plating by electrochemical deposition solves the problems of passivation and corrosion of stainless steel bipolar plates in fuel cells, improves its conductivity and corrosion resistance, and is suitable for the preparation of plating of complex substrates. Reduced manufacturing costs.
Patent Information
- Application Number
- CN202411477675.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-07
AI Technical Summary
The stainless steel bipolar plate is prone to passivation in proton exchange membrane fuel cells and proton exchange membrane water electrolytic cells, resulting in high contact resistance and corrosion, affecting battery performance.
The electrochemical deposition method is used to prepare a niobium-doped amorphous carbon composite plating, and the reduction and deposition of niobium on the stainless steel cathode is promoted by choline chloride-lactic acid-based eutectic solvent and citric acid to build a uniform niobium element-doped amorphous carbon plating. , improve conductivity and corrosion resistance.
It reduces the contact resistance and corrosion of stainless steel bipolar plates, improves its conductivity and mechanical strength, is suitable for the preparation of plating of complex substrates, and reduces manufacturing costs.
Smart Images

Figure CN119265659A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate by electrochemical deposition and its application, belonging to the field of proton exchange membrane fuel cells and proton exchange membrane water electrolysis. Background Art
[0002] As environmental problems become increasingly serious, sustainable green energy technologies are gaining more and more attention. Among them, proton exchange membrane fuel cells (PEMFC) and proton exchange membrane water electrolyzers (PEMWE) are important components of future hydrogen energy systems, and are key devices for producing hydrogen through renewable energy and utilizing hydrogen in the form of electricity, respectively. Bipolar plates are one of the key components of fuel cells and water electrolyzers, and play the role of supporting the stack, conducting current, distributing reaction gases, and conducting heat. Therefore, their performance has a vital impact on the overall performance of the battery. In order to achieve the excellent performance of PEMFC and PEMWE and promote their large-scale production, bipolar plates must have excellent corrosion resistance, low contact resistance, good mechanical properties, processability, and low cost. Although graphite materials are widely used in bipolar plates due to their excellent conductivity, their low mechanical strength and difficulty in manufacturing limit their large-scale application. Therefore, in recent years, metal materials such as stainless steel and titanium alloys have been widely studied as alternative materials for bipolar plates. However, stainless steel still faces two major challenges in practical applications: (1) Stainless steel is easily passivated in air. The presence of the passivation layer will increase the interfacial contact resistance (ICR) between the bipolar plate (BP) and the gas diffusion layer (GDL), thereby reducing the power density of PEMFC / PEMWE; (2) Although the passivation film of stainless steel can improve its corrosion resistance, corrosion will still inevitably occur in the acidic working environment of PEMFC / PEMWE, resulting in the degradation of PEMFC / PEMWE performance.
[0003] In order to solve the limitations of stainless steel in terms of corrosion resistance and conductivity, researchers have developed a variety of protective conductive functional coatings, such as transition metal nitride coatings, conductive polymer coatings, carbide coatings, and carbon-based coatings. The application of these coatings is expected to improve the performance of bipolar plates and make PEMFC / PEMWE more efficient and reliable. Among them, the advantages of amorphous carbon coatings in conductivity, chemical inertness, hardness, etc. have great application potential in the surface modification of metal bipolar plates. Amorphous carbon coatings contain a large number of nanocrystalline structures and sp 3 、sp 2 , even sp 1 Three types of disordered structures caused by hybridization, among which sp 2 The structure is beneficial to the conductivity and wear resistance of the coating, sp 3The structure is beneficial to the corrosion resistance of the coating, and the nanocrystalline structure is beneficial to the mechanical properties of the coating. Through the combination of these multifunctional properties, amorphous carbon coating can significantly improve the overall performance of bipolar plates, thereby improving the operating efficiency and life of PEMFC / PEMWE, showing great commercial application prospects.
[0004] However, the residual stress caused by bond angle deformation in the amorphous carbon coating can cause peeling between the coating and the stainless steel substrate, hindering its use as a modified coating for PEMFC / PEMWE bipolar plates. Doping metals in amorphous carbon coatings is beneficial to reducing the residual stress of the coating and improving the bonding strength between the coating and the stainless steel bipolar plate substrate. In addition, transition metals have excellent electrical conductivity and corrosion resistance. Doping amorphous carbon coatings in the form of metal elements can effectively construct a metal conductive network, further enhance the migration speed of electrons in the coating, and reduce the contact resistance between the stainless steel bipolar plate and the gas diffusion layer.
[0005] At present, the method for preparing PEMFC / PEMWE bipolar plate coatings widely used in industry is physical or chemical vapor deposition (PVD / CVD). The coatings prepared by vapor deposition have the advantages of high purity and good film uniformity, but the harsh process conditions and high preparation costs are its main constraints. Electrochemical deposition is a method with simple process, low cost and the ability to prepare coatings on complex-shaped substrates. It is widely used in industry. However, there are few reports on the use of electrochemical deposition to prepare modified amorphous carbon composite coatings for bipolar plates. Therefore, the development of a new electrochemical deposition process to prepare amorphous carbon composite coatings is of great significance for the application of PEMFC / PEMWE stainless steel bipolar plates. Summary of the invention
[0006] In view of the technical problems in the prior art of stainless steel bipolar plates of proton exchange membrane fuel cells and proton exchange membrane water electrolyzers, such as high contact resistance caused by passivation and battery failure caused by corrosion, the present invention provides a method and application of preparing niobium-doped amorphous carbon composite coating modified stainless steel bipolar plates by a simple electrochemical deposition method.
[0007] The present invention provides a composite coating with good electrical conductivity and corrosion resistance, which is composed of a metal single substance niobium doped amorphous carbon coating. In the composite coating, methyl radicals generated by the decomposition of choline chloride-lactic acid-based low eutectic solvent under the action of an electric field serve as the main film-forming substance of the coating, and are reduced and deposited on stainless steel to form an amorphous carbon coating. The complexation of citric acid with niobium ions in the solution promotes the reduction and deposition of niobium on the cathode of the stainless steel. At the same time, the adsorption of citric acid on the cathode provides more active sites for the reduction of niobium, which is beneficial to the doping and deposition of single substance niobium, and constructs an amorphous carbon composite coating uniformly doped with single substance niobium. The amorphous carbon coating is composed of sp 2 and sp 3The hybrid carbon provides the stainless steel bipolar plate with excellent corrosion resistance and low contact resistance, while the uniformly doped niobium element constructs an interwoven metal conductive network in the coating, which promotes the migration and movement of electrons in the coating, further improving the conductivity of the coating.
[0008] In order to achieve the above object, the technical solution of the present invention is as follows:
[0009] In one aspect, the present invention provides a method for preparing a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate by electrochemical deposition, the method comprising the following steps:
[0010] S1. Pre-treating the stainless steel bipolar plate to obtain a stainless steel bipolar plate to be used;
[0011] S2, connecting the standby stainless steel bipolar plate obtained in step S1 to the negative electrode of a DC electroplating power source as a cathode, connecting the anode plate to the positive electrode of a DC electroplating power source as an anode, placing the cathode and the anode in parallel in a composite electroplating solution, and performing electrochemical deposition by a constant potential deposition method to obtain a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate;
[0012] In step S2, the composite electroplating solution is composed of a choline chloride-lactic acid-based deep eutectic solvent prepared from choline chloride and lactic acid in a molar ratio of 1:0.5 to 1:4, 0.01 to 0.05 mol / L of niobium pentachloride and 0.1 to 0.5 mol / L of citric acid.
[0013] In the above technical solution, further, in step S1, the pretreatment process of the stainless steel bipolar plate is:
[0014] The stainless steel bipolar plate is polished and ground with SiC sandpaper of models 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and then ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it is placed in an alkaline degreasing solution and soaked for 2 to 20 minutes at 40 to 70° C. for degreasing treatment. After cleaning with deionized water, it is soaked in a composite acid cleaning solution for 20 seconds to 5 minutes for surface activation, and finally ultrasonically cleaned with deionized water for use.
[0015] In the above technical solution, further, the alkaline degreasing liquid is prepared by mixing 60g / L NaOH, 30g / L Na2CO3 and 20g / L Na3PO4;
[0016] The composite pickling solution is prepared by mixing 20% by volume of HNO3, 5% by volume of HF and 75% by volume of water.
[0017] In the above technical solution, further, in step S2, the method for preparing the composite electroplating solution comprises the following steps:
[0018] S2-1, placing choline chloride and lactic acid in a constant temperature water bath and stirring them in a closed environment until a colorless transparent solution is obtained, the stirring temperature is 50-80° C., and the stirring time is 4-6 hours, to prepare a choline chloride-lactic acid-based low eutectic solvent, and storing it in a constant temperature vacuum box at 70° C. for standby use;
[0019] S2-2, adding niobium pentachloride to a choline chloride-lactic acid-based low eutectic solvent, heating in a constant temperature water bath with stirring for 2 to 5 hours, the stirring temperature being 50 to 80° C., to obtain a milky white basic electroplating solution;
[0020] S2-3, adding citric acid to the basic electroplating solution obtained in step S2-2, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution.
[0021] In the above technical solution, further, in step S2, the conditions of the electrochemical deposition are: the deposition potential is -2 to -4 V, the temperature of the composite electroplating solution is 50 to 90° C., and the deposition time is 30 to 180 min.
[0022] In the above technical solution, further, in step S2, the anode plate is a high-purity graphite plate or a pre-treated niobium plate;
[0023] The pretreatment process of the niobium plate is as follows: rinse the niobium plate with deionized water to remove surface contaminants, then place the niobium plate in anhydrous ethanol solution for ultrasonic cleaning for 3 to 5 minutes to remove grease, and finally clean it with deionized water for use.
[0024] In the above technical solution, further, the niobium-doped amorphous carbon composite coating is composed of amorphous carbon and niobium element, the niobium element is uniformly doped in the amorphous carbon, and the amorphous carbon constitutes the main coating component.
[0025] Another aspect of the present invention provides an application of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared by the above method in a proton exchange membrane fuel cell.
[0026] The present invention also provides an application of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared by the above method in proton exchange membrane water electrolysis.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention utilizes the wider electrochemical window of the choline chloride-lactic acid eutectic solvent than the aqueous solution, and can reduce the niobium ions that cannot be reduced in the aqueous electrolyte into niobium element, and uniformly dope it into the coating during the film formation process, thereby obtaining a continuous and dense niobium-doped amorphous carbon composite coating.
[0029] 2. Citric acid acts as a chelating agent to complex with niobium ions in the electroplating solution, which promotes the deposition of niobium on the stainless steel cathode. In addition, citric acid is easily adsorbed on the electrode, providing more reduction sites for the reduction of niobium.
[0030] 3. Niobium-doped amorphous carbon composite coating has excellent corrosion resistance and conductivity, in which amorphous carbon as the main component of the coating is composed of sp 2 Hybridized carbon and sp 3 Hybridized carbon composition, among which sp 2 Carbon contributes to the conductivity of the coating, sp 3 Carbon has good electrochemical stability. Niobium is uniformly dispersed and doped in the composite coating in the form of a single substance to build a metal conductive network, providing a faster channel for the conduction and transportation of electrons, meeting the requirements of PEMFC / PEMWE for low contact resistance of bipolar plates.
[0031] 4. The present invention adopts an electrochemical deposition method with low cost and simple process. Compared with other bipolar plate modified coating preparation methods, it is more suitable for metal bipolar plate substrates with complex flow channels. The prepared niobium-doped amorphous carbon composite coating has the advantages of dense uniformity and strong bonding force, which greatly reduces the manufacturing cost of PEMFC / PEMWE bipolar plate coatings.
[0032] 5. The niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared by the present invention has excellent electrochemical stability and conductivity, as well as excellent mechanical strength and adhesion, and can fully exert the synergistic effect of the composite coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.
[0034] Figure 1 This is a scanning electron microscope image of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1, with a scale of 200 nm;
[0035] Figure 2 The Raman spectrum of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1;
[0036] Figure 3 This is a transmission electron microscope image of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1;
[0037] Figure 4 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1;
[0038] Figure 50.6V (vs Ag / AgCl) constant potential polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1;
[0039] Figure 6 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 2;
[0040] Figure 7 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 3;
[0041] Figure 8 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 6;
[0042] Fig. 9 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 7;
[0043] Fig.10 This is a contact resistance curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1. DETAILED DESCRIPTION
[0044] In order to clearly express the purpose and specific implementation scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0045] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0046] Example 1
[0047] A preparation method and application of a stainless steel bipolar plate modified by electrochemical deposition of niobium-doped amorphous carbon composite coating, comprising the following steps:
[0048] (1) The 316L stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it was placed in an alkaline degreasing solution with the composition of 60g / L NaOH+30g / L Na2CO3+20g / L Na3PO4, and soaked at 60°C for 10 minutes for degreasing treatment. After cleaning with deionized water, it was placed in a composite acid cleaning solution prepared by mixing 20% by volume HNO3, 5% HF and 75% water for 1 minute for surface activation, and finally ultrasonically cleaned with deionized water for use;
[0049] (2) Weigh choline chloride and lactic acid in a molar ratio of 1:2, place in a constant temperature water bath environment and stir in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 5 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, which is stored in a constant temperature vacuum box at 70° C. for later use;
[0050] (3) Weighing 0.03 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based low eutectic solvent, heating and stirring in a water bath for 4 hours, the stirring temperature is 70° C., and a milky white basic electroplating solution is obtained;
[0051] (4) Weighing 0.3 mol / L citric acid and adding it to the milky white basic electroplating solution of choline chloride-lactic acid-niobium pentachloride, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution;
[0052] (5) Rinse the niobium plate in deionized water to remove surface contaminants, then place it in an anhydrous ethanol solution for ultrasonic cleaning for 5 minutes to remove grease, and finally rinse it with deionized water for later use;
[0053] (6) Connecting the stainless steel bipolar plate treated in step (1) to the negative electrode of a DC electroplating power source as a cathode, connecting the niobium plate treated in step (5) to the positive electrode of a DC electroplating power source as an anode, placing the cathode and the anode in parallel in the composite electroplating solution prepared in step (4), using a constant potential deposition method, with a deposition potential of -3 V, heating the composite electroplating solution in a constant temperature water bath at 70° C. for a deposition time of 180 min, obtaining a niobium-doped amorphous carbon composite coating on the surface of the stainless steel bipolar plate, and obtaining a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate.
[0054] Figure 1 This is a scanning electron microscope image of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1. It can be seen from the figure that the coating is densely coated on the 316L substrate, which is mainly composed of fine particles with a size of several to tens of nanometers. The coating structure is fine and tight without obvious damage and voids.
[0055] Figure 2 The Raman spectrum of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1 is Figure 2 The peak fitting of carbon shows that the peak at 1365 cm -1 (D peak) and 1595cm -1 The D peak is usually related to the sp 2 The G peak is related to the stretching vibration of the C-C bond of the carbon atom, while the sp 2 The peak area ratio of ID / IG means that C-sp 2 It can be clearly seen that for the obtained coating, the intensity of the fitted D peak is significantly higher than the intensity of the fitted G peak (ID / IG=2.19). This means that the coating has a high C-sp 2 ratio, which may contribute to the high conductivity
[0056] Figure 3 This is a transmission electron microscope image of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1. The coating is a composite coating composed of amorphous carbon and niobium, and the intercrystalline spacings thereof are 0.168 nm and 0.238 nm, respectively, corresponding to the (200) and (100) crystal planes of Nb.
[0057] Example 2
[0058] (1) The 316L stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it was placed in an alkaline degreasing solution with the composition of 60g / L NaOH+30g / L Na2CO3+20g / L Na3PO4, and soaked at 60°C for 10 minutes for degreasing treatment. After cleaning with deionized water, it was placed in a composite acid cleaning solution prepared by mixing 20% by volume HNO3, 5% HF and 75% water for 1 minute for surface activation, and finally ultrasonically cleaned with deionized water for use;
[0059] (2) Weigh choline chloride and lactic acid in a molar ratio of 1:2, place in a constant temperature water bath environment and stir in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 5 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared and stored in a constant temperature vacuum box at 70° C. for later use;
[0060] (3) Weighing 0.03 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based low eutectic solvent, heating and stirring in a water bath for 4 hours, the stirring temperature is 70° C., and a milky white basic electroplating solution is obtained;
[0061] (4) Weighing 0.2 mol / L citric acid and adding it to the milky white basic electroplating solution of choline chloride-lactic acid-niobium pentachloride, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution;
[0062] (5) Rinse the niobium plate in deionized water to remove surface contaminants, then place it in an anhydrous ethanol solution for ultrasonic cleaning for 5 minutes to remove grease, and finally rinse it with deionized water for later use;
[0063] (6) Connecting the stainless steel bipolar plate treated in step (1) to the negative electrode of the electroplating power supply as a cathode, connecting the niobium plate treated in step (5) to the positive electrode of the DC electroplating power supply as an anode, placing the cathode and the anode in parallel in the composite electroplating solution prepared in step (4), using a constant potential deposition method, the deposition potential is -3 V, the electroplating solution is heated in a constant temperature water bath at 70° C., and the deposition time is 180 min, to obtain a niobium-doped amorphous carbon composite coating on the surface of the stainless steel bipolar plate, thereby obtaining a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate.
[0064] Example 3
[0065] (1) The stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and then ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it was placed in an alkaline degreasing solution, the composition of which was: 60g / L NaOH+30g / L Na2CO3+20g / L Na3PO4, and soaked at 60°C for 10 minutes for degreasing treatment. After cleaning with deionized water, it was placed in a composite acid cleaning solution prepared by mixing 20% by volume HNO3, 5% HF and 75% water and soaked for 1 minute for surface activation. Finally, it was ultrasonically cleaned with deionized water and set aside;
[0066] (2) Weigh choline chloride and lactic acid in a molar ratio of 1:2, place in a constant temperature water bath environment and stir in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 5 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared and stored in a constant temperature vacuum box at 70° C. for later use;
[0067] (3) Weighing 0.03 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based low eutectic solvent, heating and stirring in a water bath for 4 hours, the stirring temperature is 70° C., and a milky white basic electroplating solution is obtained;
[0068] (4) Weighing 0.5 mol / L citric acid and adding it to the milky white basic electroplating solution of choline chloride-lactic acid-niobium pentachloride, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution;
[0069] (5) Rinse the niobium plate in deionized water to remove surface contaminants, then place it in an anhydrous ethanol solution for ultrasonic cleaning for 5 minutes to remove grease, and finally rinse it with deionized water for later use;
[0070] (6) Connecting the stainless steel bipolar plate treated in step (1) to the negative electrode of the electroplating power supply as a cathode, connecting the niobium plate treated in step (5) to the positive electrode of the DC electroplating power supply as an anode, placing the cathode and the anode in parallel in the composite electroplating solution prepared in step (4), using a constant potential deposition method, the deposition potential is -3 V, the electroplating solution is heated in a constant temperature water bath at 70° C., and the deposition time is 180 min, to obtain a niobium-doped amorphous carbon composite coating on the surface of the stainless steel bipolar plate, thereby obtaining a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate.
[0071] Example 4
[0072] A preparation method and application of a stainless steel bipolar plate modified by electrochemical deposition of niobium-doped amorphous carbon composite coating, comprising the following steps:
[0073] (1) The 316L stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and then ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it was placed in an alkaline degreasing solution with the composition of 60g / L NaOH+30g / L Na2CO3+20g / LNa3PO4, and soaked for 10 minutes at 60°C for degreasing treatment. After cleaning with deionized water, it was placed in a composite acid cleaning solution prepared by mixing 20% by volume HNO3, 5% HF and 75% water for 1 minute for surface activation, and finally ultrasonically cleaned with deionized water for use;
[0074] (2) Weigh choline chloride and lactic acid in a molar ratio of 1:0.5, place in a constant temperature water bath environment and stir in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 5 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, which is stored in a constant temperature vacuum box at 70° C. for later use;
[0075] (3) Weighing 0.03 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based low eutectic solvent, heating and stirring in a water bath for 4 hours, the stirring temperature is 70° C., and a milky white basic electroplating solution is obtained;
[0076] (4) Weighing 0.3 mol / L citric acid and adding it to the milky white base electroplating solution, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution;
[0077] (5) Rinse the niobium plate in deionized water to remove surface contaminants, then place it in an anhydrous ethanol solution for ultrasonic cleaning for 5 minutes to remove grease, and finally rinse it with deionized water for later use;
[0078] (6) Connecting the stainless steel bipolar plate treated in step (1) to the negative electrode of a DC electroplating power source as a cathode, connecting the niobium plate treated in step (5) to the positive electrode of a DC electroplating power source as an anode, placing the cathode and the anode in parallel in the composite electroplating solution prepared in step (4), using a constant potential deposition method, with a deposition potential of -3 V, heating the composite electroplating solution in a constant temperature water bath at 70° C. for a deposition time of 180 min, obtaining a niobium-doped amorphous carbon composite coating on the surface of the stainless steel bipolar plate, and obtaining a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate.
[0079] Example 5
[0080] A preparation method and application of a stainless steel bipolar plate modified by electrochemical deposition of niobium-doped amorphous carbon composite coating, comprising the following steps:
[0081] (1) The 316L stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and then ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it was placed in an alkaline degreasing solution with the composition of 60g / L NaOH+30g / L Na2CO3+20g / LNa3PO4, and soaked for 10 minutes at 60°C for degreasing treatment. After cleaning with deionized water, it was placed in a composite acid cleaning solution prepared by mixing 20% by volume HNO3, 5% HF and 75% water for 1 minute for surface activation, and finally ultrasonically cleaned with deionized water for use;
[0082] (2) Weigh choline chloride and lactic acid in a molar ratio of 1:4, place in a constant temperature water bath environment and stir in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 5 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, which is stored in a constant temperature vacuum box at 70° C. for later use;
[0083] (3) Weighing 0.03 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based low eutectic solvent, heating and stirring in a water bath for 4 hours, the stirring temperature is 70° C., and a milky white basic electroplating solution is obtained;
[0084] (4) Weighing 0.3 mol / L citric acid and adding it to the milky white base electroplating solution, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution;
[0085] (5) Rinse the niobium plate in deionized water to remove surface contaminants, then place it in an anhydrous ethanol solution for ultrasonic cleaning for 5 minutes to remove grease, and finally rinse it with deionized water for later use;
[0086] (6) Connecting the stainless steel bipolar plate treated in step (1) to the negative electrode of a DC electroplating power source as a cathode, connecting the niobium plate treated in step (5) to the positive electrode of a DC electroplating power source as an anode, placing the cathode and the anode in parallel in the composite electroplating solution prepared in step (4), using a constant potential deposition method, with a deposition potential of -3 V, heating the composite electroplating solution in a constant temperature water bath at 70° C. for a deposition time of 180 min, obtaining a niobium-doped amorphous carbon composite coating on the surface of the stainless steel bipolar plate, and obtaining a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate.
[0087] Example 6
[0088] A preparation method and application of a stainless steel bipolar plate modified by electrochemical deposition of niobium-doped amorphous carbon composite coating, comprising the following steps:
[0089] (1) The 316L stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and then ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it was placed in an alkaline degreasing solution with the composition of 60g / L NaOH+30g / L Na2CO3+20g / LNa3PO4, and soaked for 10 minutes at 60°C for degreasing treatment. After cleaning with deionized water, it was placed in a composite acid cleaning solution prepared by mixing 20% by volume HNO3, 5% HF and 75% water for 1 minute for surface activation, and finally ultrasonically cleaned with deionized water for use;
[0090] (2) Weigh choline chloride and lactic acid in a molar ratio of 1:2, place in a constant temperature water bath environment and stir in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 5 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, which is stored in a constant temperature vacuum box at 70° C. for later use;
[0091] (3) Weighing 0.01 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based low eutectic solvent, heating and stirring in a water bath for 4 hours, the stirring temperature is 70° C., and a milky white basic electroplating solution is obtained;
[0092] (4) Weighing 0.3 mol / L citric acid and adding it to the milky white base electroplating solution, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution;
[0093] (5) Rinse the niobium plate in deionized water to remove surface contaminants, then place it in an anhydrous ethanol solution for ultrasonic cleaning for 5 minutes to remove grease, and finally rinse it with deionized water for later use;
[0094] (6) Connecting the stainless steel bipolar plate treated in step (1) to the negative electrode of a DC electroplating power source as a cathode, connecting the niobium plate treated in step (5) to the positive electrode of a DC electroplating power source as an anode, placing the cathode and the anode in parallel in the composite electroplating solution prepared in step (4), using a constant potential deposition method, with a deposition potential of -3 V, heating the composite electroplating solution in a constant temperature water bath at 70° C. for a deposition time of 180 min, obtaining a niobium-doped amorphous carbon composite coating on the surface of the stainless steel bipolar plate, and obtaining a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate.
[0095] Example 7
[0096] A preparation method and application of a stainless steel bipolar plate modified by electrochemical deposition of niobium-doped amorphous carbon composite coating, comprising the following steps:
[0097] (1) The 316L stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and then ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it was placed in an alkaline degreasing solution with the composition of 60g / L NaOH+30g / L Na2CO3+20g / LNa3PO4, and soaked for 10 minutes at 60°C for degreasing treatment. After cleaning with deionized water, it was placed in a composite acid cleaning solution prepared by mixing 20% by volume HNO3, 5% HF and 75% water for 1 minute for surface activation, and finally ultrasonically cleaned with deionized water for use;
[0098] (2) Weigh choline chloride and lactic acid in a molar ratio of 1:2, place in a constant temperature water bath environment and stir in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 5 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, which is stored in a constant temperature vacuum box at 70° C. for later use;
[0099] (3) Weighing 0.05 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based low eutectic solvent, heating and stirring in a water bath for 4 h, the stirring temperature is 70° C., and a milky white basic electroplating solution is obtained;
[0100] (4) Weighing 0.3 mol / L citric acid and adding it to the milky white base electroplating solution, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution;
[0101] (5) Rinse the niobium plate in deionized water to remove surface contaminants, then place it in an anhydrous ethanol solution for ultrasonic cleaning for 5 minutes to remove grease, and finally rinse it with deionized water for later use;
[0102] (6) Connecting the stainless steel bipolar plate treated in step (1) to the negative electrode of a DC electroplating power source as a cathode, connecting the niobium plate treated in step (5) to the positive electrode of a DC electroplating power source as an anode, placing the cathode and the anode in parallel in the composite electroplating solution prepared in step (4), using a constant potential deposition method, with a deposition potential of -3 V, heating the composite electroplating solution in a constant temperature water bath at 70° C. for a deposition time of 180 min, obtaining a niobium-doped amorphous carbon composite coating on the surface of the stainless steel bipolar plate, and obtaining a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate.
[0103] Test Example 1
[0104] Test conditions: The electrolyte was 0.5M H2SO4 and 5ppm HF solution, the reference electrode was Ag / AgCl, the counter electrode was a platinum mesh, the working electrode was the prepared niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate, and the test area was 1cm 2 , test temperature 80℃, air passing through the electrolyte.
[0105] Figure 4 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (Acm -2 )). Compared with 316L stainless steel, the stainless steel modified by niobium-doped amorphous carbon composite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 Acm -2 Reduced to 9.36×10 -7 Acm -2 .
[0106] Figure 5 0.6V (vs Ag / AgCl) constant potential polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1; the horizontal axis in the figure is time (h), and the vertical axis is current density (A cm -2 The current density of the niobium-doped amorphous carbon composite coating remained stable within 24 hours, and the corrosion current density was significantly lower than that of the bare stainless steel plate, indicating that it can effectively protect the stainless steel from corrosion under simulated cathode conditions and exhibit excellent electrochemical stability.
[0107] Figure 6The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 2; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (Acm -2 )). Compared with 316L stainless steel, the stainless steel modified by niobium-doped amorphous carbon composite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 A cm -2 Reduced to 2.55×10 -6 A cm -2 .
[0108] Figure 7 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 3; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (Acm -2 )). Compared with 316L stainless steel, the stainless steel modified by niobium-doped amorphous carbon composite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 A cm -2 Reduced to 3.04×10 -6 A cm -2 .
[0109] Figure 8 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 6; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (Acm -2 )). Compared with 316L stainless steel, the stainless steel modified by niobium-doped amorphous carbon composite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 A cm -2 Reduced to 1.46×10 -6 A cm -2 .
[0110] Fig. 9 The potentiodynamic polarization curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 7; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (Acm -2)). Compared with 316L stainless steel, the stainless steel modified by niobium-doped amorphous carbon composite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 A cm -2 Reduced to 2.45×10 -6 A cm -2 .
[0111] Test Example 2
[0112] Test conditions: The sample is placed between two gold-plated copper electrodes with the carbon paper used for the fuel cell diffusion layer on both sides as support. A certain pressure is applied on both sides of the copper electrode, and the resistance value under different applied pressures is obtained by recording the current and resistance value under different pressures. The support layer uses the carbon paper used for the fuel cell diffusion layer; the electrode uses a gold-plated metal electrode, generally a gold-plated copper electrode.
[0113] Fig.10 The contact resistance curve of the niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared in Example 1; the horizontal axis in the figure is the applied pressure (Pressure (MPa)), and the vertical axis is the contact resistance (ICR (mΩcm 2 )). As can be seen from the figure, as the pressure increases, the contact resistance first drops sharply, and then slowly drops under high pressure. In the entire pressure range, the contact resistance of the stainless steel modified by the coating is much lower than that of 316L stainless steel.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate by electrochemical deposition, characterized in that: The method comprises the following steps: S1. Pre-treating the stainless steel bipolar plate to obtain a stainless steel bipolar plate to be used; S2, connecting the standby stainless steel bipolar plate obtained in step S1 to the negative electrode of a DC electroplating power source as a cathode, connecting the anode plate to the positive electrode of a DC electroplating power source as an anode, placing the cathode and the anode in parallel in a composite electroplating solution, and performing electrochemical deposition by a constant potential deposition method to obtain a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate; In step S2, the composite electroplating solution is composed of a choline chloride-lactic acid-based deep eutectic solvent prepared from choline chloride and lactic acid in a molar ratio of 1:0.5 to 1:4, 0.01 to 0.05 mol / L of niobium pentachloride and 0.1 to 0.5 mol / L of citric acid.
2. The method according to claim 1, characterized in that In step S1, the pretreatment process of the stainless steel bipolar plate is as follows: The stainless steel bipolar plate is polished and ground with SiC sandpaper of models 400#, 800#, 1200#, and 2000# in turn to remove the passivation film on the stainless steel surface, rinsed with deionized water, and then ultrasonically cleaned in anhydrous ethanol solution for 20 minutes. After cleaning, it is placed in an alkaline degreasing solution and soaked for 2 to 20 minutes at 40 to 70° C. for degreasing treatment. After cleaning with deionized water, it is soaked in a composite acid cleaning solution for 20 seconds to 5 minutes for surface activation, and finally ultrasonically cleaned with deionized water for use.
3. The method according to claim 2, characterized in that The alkaline degreasing solution is prepared by mixing 60 g / L NaOH, 30 g / L Na2CO3 and 20 g / L Na3PO4; The composite pickling solution is prepared by mixing 20% by volume of HNO3, 5% by volume of HF and 75% by volume of water.
4. The method according to claim 1, characterized in that: In step S2, the method for preparing the composite electroplating solution comprises the following steps: S2-1, placing choline chloride and lactic acid in a constant temperature water bath and stirring them in a closed environment until a colorless transparent solution is obtained, the stirring temperature is 50-80° C., and the stirring time is 4-6 hours, to prepare a choline chloride-lactic acid-based low eutectic solvent, and storing it in a constant temperature vacuum box at 70° C. for standby use; S2-2, adding niobium pentachloride to a choline chloride-lactic acid-based low eutectic solvent, heating in a constant temperature water bath with stirring for 2 to 5 hours, the stirring temperature being 50 to 80° C., to obtain a milky white basic electroplating solution; S2-3, adding citric acid to the basic electroplating solution obtained in step S2-2, stirring until the citric acid is completely dissolved, to obtain a composite electroplating solution.
5. The method according to claim 1, characterized in that: In step S2, the conditions of the electrochemical deposition are: deposition potential of -2 to -4 V, composite electroplating solution temperature of 50 to 90° C., and deposition time of 30 to 180 min.
6. The method according to claim 1, characterized in that In step S2, the anode plate is a high-purity graphite plate or a pre-treated niobium plate; The pretreatment process of the niobium plate is as follows: rinse the niobium plate with deionized water to remove surface contaminants, then place the niobium plate in anhydrous ethanol solution for ultrasonic cleaning for 3 to 5 minutes to remove grease, and finally clean it with deionized water for use.
7. The method according to claim 1, characterized in that The niobium-doped amorphous carbon composite coating is composed of amorphous carbon and niobium simple substance, and the niobium simple substance is uniformly doped in the amorphous carbon coating.
8. Use of a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared by the method according to any one of claims 1 to 7 in a proton exchange membrane fuel cell.
9. Use of a niobium-doped amorphous carbon composite coating modified stainless steel bipolar plate prepared by the method according to any one of claims 1 to 7 in proton exchange membrane water electrolysis.